2017
DOI: 10.1016/j.celrep.2017.03.047
|View full text |Cite
|
Sign up to set email alerts
|

An Organoid-Based Model of Cortical Development Identifies Non-Cell-Autonomous Defects in Wnt Signaling Contributing to Miller-Dieker Syndrome

Abstract: Miller-Dieker syndrome (MDS) is caused by a heterozygous deletion of chromosome 17p13.3 involving the genes LIS1 and YWHAE (coding for 14.3.3ε) and leads to malformations during cortical development. Here, we used patient-specific forebrain-type organoids to investigate pathological changes associated with MDS. Patient-derived organoids are significantly reduced in size, a change accompanied by a switch from symmetric to asymmetric cell division of ventricular zone radial glia cells (vRGCs). Alterations in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
217
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(237 citation statements)
references
References 31 publications
9
217
0
2
Order By: Relevance
“…A switch from symmetric to asymmetric cell division of apical RGCs was observed, as well as alterations of the N-Cadherin/β-Catenin signaling pathway, showing that a reduction of Wnt activity leads to premature neurogenesis. These alterations in MDS-derived organoids were rescued by Wnt activation [299]. Thus, these studies highlight the potential of organotypic cell-culture models to contribute to the understanding of developmental mechanisms underlying MCDs.…”
Section: Stem Cell Models As Tools For the Study Of MCD Mechanismsmentioning
confidence: 66%
See 1 more Smart Citation
“…A switch from symmetric to asymmetric cell division of apical RGCs was observed, as well as alterations of the N-Cadherin/β-Catenin signaling pathway, showing that a reduction of Wnt activity leads to premature neurogenesis. These alterations in MDS-derived organoids were rescued by Wnt activation [299]. Thus, these studies highlight the potential of organotypic cell-culture models to contribute to the understanding of developmental mechanisms underlying MCDs.…”
Section: Stem Cell Models As Tools For the Study Of MCD Mechanismsmentioning
confidence: 66%
“…It was also shown that MDS bRG cells remained in mitosis for prolonged periods prior to cytokinesis and thus, authors suggest the possible involvement of bRG cell dysfunction in the pathogenesis of human LIS [298]. A second study has also used patient-specific forebrain-type organoids to study MDS pathology [299]. Premature neurogenesis was found to reduce the expansion of MDS patient-specific organoids, characterized with a panel of parameters.…”
Section: Stem Cell Models As Tools For the Study Of MCD Mechanismsmentioning
confidence: 99%
“…The organoids also displayed severe apoptosis of neuroepithelial stem cells in the ventricular-like zone and a mitotic defect in oRGs 50 . A second report also observed changes in the division mode of radial glial cells in MDS organoids and identified non-cell-autonomous defects in WNT signalling as an underlying mechanism 67 .…”
Section: Organoids As Models Of Brain Diseasementioning
confidence: 91%
“…However, they can also be used to discover human-specific phenotypes, providing an advantage over existing mouse models. Two recent papers used brain organoids to investigate the cellular basis of Miller–Dieker syndrome (MDS), a severe congenital form of lissencephaly 50,67 . Classically, lissencephaly has been studied in mouse models, which have the obvious disadvantage of being naturally lissencephalic.…”
Section: Organoids As Models Of Brain Diseasementioning
confidence: 99%
“…Their results identified several cellular features of this classical form of lissencephaly, including aberrant cell cycle of outer radial glia and non–cell‐autonomous alteration of WNT signaling 42, 43…”
Section: Translational Applications Of Brain Organoidsmentioning
confidence: 99%